Relacionamentos entre controle gerencial, aprendizagem organizacional e decisões - José Carlos Tiomatsu Oyadomari (Revista Contemporânea de Contabilidade, 2013)
The current dynamic and competitive scenario requires th at organizations be able to retain information from the environment in which they are inserted and use this knowledge to improve their performance through decisions based on the usage of a Management Control System. The aim of this study is to identify the relationships among Management Control System Use, Organizational Learning and Decisionmaking in Brazilian companies. The study is innovative when proposes a set of decisions based on the related literature. It was concluded that there is a positive rela tionship among the variables. The results also suggest that the Organizational Structure influences Organizational Learning, which encourag es the search for new knowledge . Consequently, this influences the decisionmaking process positively .